Comparative effects of different antiplatelet strategies in carriers of CYP2C19 loss-of-function alleles: a network meta-analysis - Galli, Mattia; Occhipinti, Giovanni; Benenati, Stefano; Laborante, Renzo; Ortega-Paz, Luis; Franchi, Francesco; D'Amario, Domenico; Nerla, Roberto; Castriota, Fausto; Frati, Giacomo; Biondi-Zoccai, Giuseppe; Sciarretta, Sebastiano; et al. (European heart journal. Cardiovascular pharmacotherapy, 2024)
Background Carriers of cytochrome 2C19 (CYP2C19) loss-of-function (LoF) alleles treated with clopidogrel have impaired drug metabolism, resulting in reduced active metabolite levels, high platelet reactivity (HPR), and an increased risk of thrombotic events. Several alternative antiplatelet therapies have been proposed to overcome HPR in these patients, but their comparative effects remain poorly explored. Methods Randomized controlled trials (RCTs) comparing different oral antiplatelet therapies in carriers of CYP2C19 LoF alleles undergoing percutaneous coronary interventions (PCI) were included. A frequentist network meta-analysis was conducted to estimate mean difference (MD) or odds ratios and 95% confidence intervals (CI). The primary outcome was platelet reactivity assessed by VerifyNow and reported as P2Y12 reaction unit (PRU). The secondary outcome was the rate of HPR. Standard dose of clopidogrel (75 mg daily) was used as a reference treatment. Results A total of 12 RCTs testing 6 alternative strategies (i.e. clopidogrel 150 mg, prasugrel 3.75 mg, 5 mg, and 10 mg, ticagrelor 90 mg bid, and adjunctive cilostazol 100 mg bid) were included in the network. Compared with standard-dose clopidogrel, the greatest reduction in PRU was observed with prasugrel 10 mg (MD −127.91; 95% CI −141.04; −114.78) and ticagrelor 90 mg bid (MD −124.91; 95% CI −161.78; −88.04), followed by prasugrel 5 mg (MD −76.33; 95% CI −98.01; −54.65) and prasugrel 3.75 mg (MD −73.00; 95% CI −100.28; −45.72). Among other strategies, adjunctive cilostazol (MD −42.64; 95% CI −64.72; −20.57) and high-dose clopidogrel (MD −32.11; 95% CI −51.33; −12.90) were associated with a modest reduction in PRU compared with standard-dose clopidogrel. Conclusion Among carriers of CYP2C19 LoF alleles undergoing PCI, standard-dose prasugrel or ticagrelor are most effective in reducing platelet reactivity, while double-dose clopidogrel and additional cilostazol showed modest effects. Reduced-dose of prasugrel may represent a balanced strategy to overcome HPR without a significant increase in bleeding. The clinical implications of these pharmacodynamic findings warrant further investigation. Graphical Abstract Graphical Abstract